Importance of Biomechanical Pose Analysis of Young Players Using Mobile Videos and Comparing the Efficiency with Classical Biomechanics - Manu, Abhilash; D, Ganesh (Journal of Neonatal Surgery, 2025)
Biomechanical analysis in tennis has become a critical area of research, enhancing performance optimization, injury prevention, and technique refinement. This paper explores the significance of biomechanical studies in tennis, highlighting key techniques such as motion capture, force plate analysis, electromyography (EMG), and computational modelling. We analyse how biomechanics influences stroke mechanics, footwork, energy efficiency, and injury mitigation. Furthermore, we compare and discuss recent advancements in deep learning and AI-driven pose estimation for real-time player analysis, comparing them with traditional camera-based techniques.